2022
DOI: 10.3390/info13090414
|View full text |Cite
|
Sign up to set email alerts
|

Information Adoption Patterns and Online Knowledge Payment Behavior: The Moderating Role of Product Type

Abstract: The development of online knowledge payment platforms in recent years has increased their respective market value by nurturing content resources and improving content ecology. Yet, the underlying factors of knowledge seekers’ payment behaviors and their information adoption mechanisms are poorly understood. Based on the information adoption model, this study develops a research model to examine the relationship between information adoption patterns and knowledge seekers’ payment behavior, and explore the moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Trust in online knowledge payment and identification with knowledge contributors both significantly influence consumers' purchase intentions, whereas trust in the platform does not affect either consumers' trust in online knowledge payment or their purchase intentions. Based on the information adoption model, Daradkeh [49] established a new research model and used a combination of text and regression analysis to examine the relationship between information adoption patterns and knowledge acquirers' payment behavior, as well as to explore the moderating effect of product type on this relationship. The results showed that the completeness, vividness, and relevance of product descriptions had a significant positive impact on knowledge payment behavior, and the reputation, experience, and integrity of knowledge providers had a positive impact on knowledge payment behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Trust in online knowledge payment and identification with knowledge contributors both significantly influence consumers' purchase intentions, whereas trust in the platform does not affect either consumers' trust in online knowledge payment or their purchase intentions. Based on the information adoption model, Daradkeh [49] established a new research model and used a combination of text and regression analysis to examine the relationship between information adoption patterns and knowledge acquirers' payment behavior, as well as to explore the moderating effect of product type on this relationship. The results showed that the completeness, vividness, and relevance of product descriptions had a significant positive impact on knowledge payment behavior, and the reputation, experience, and integrity of knowledge providers had a positive impact on knowledge payment behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies have explored the impact on users’ intentions to purchase, mainly from the perspectives of information contributors and the characteristics of the information itself. From the perspectives of online information contributors, it has been found that reputation, the number of times of free online information sharing, whether there is real name authentication, and the experience and integrity of online information contributors can significantly affect users’ purchase intentions [ 18 ]. From the perspective of the characteristics of online information itself, previous studies have shown that the perceived quality of free content, the number of participants, price, and perceived value can all positively influence users’ purchase intentions [ 19 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…VoI can be formally defined using two alternative perspectives: (1) assessing a potential user's willingness to pay for obtaining access to the knowledge [34,35]; or (2) the increase in expected benefit that arises from acting according to the best choice with the presence of the information compared to the expected benefit when no information is available [34,36]. The concept of VoI has become highly relevant now that information sharing is a daily activity; indeed, VoI analysis is used in varied fields, including health-economic evaluations [37], supply-chain decisions [38], online knowledge payment platforms [39], earth sciences [40], and auction research [41,42]. VoI can be measured both in cases with full disclosure, i.e., the information provided eliminates the uncertainty entirely [43], and in those with partial disclosure in which the information provided eliminates only part of the uncertainty [44].…”
Section: Related Workmentioning
confidence: 99%